Genetic Assay for Small Fragments of Bacteriophage φX174 Deoxyribonucleic Acid - Hutchison, Clyde A. (1971)
The double-stranded replicative form deoxyribonucleic acid (RF-DNA) of bacteriophage φX174 was fragmented by pancreatic deoxyribonuclease, and the complementary strand fragments were then annealed to intact viral single strands. When such complexes infected Escherichia coli spheroplasts, some of the progeny virus bore genetic markers derived from the RF-DNA fragments. In this way, genetic markers have been salvaged from DNA fragments less than 50 nucleotides in length. This method is potentially useful as a specific assay to aid in the purification of genetically defined DNA fragments and also as a mechanism for the incorporation of small chemically synthesized DNA sequences into viral genomes.